Networked Field Studies: Comparative Inquiry and Online Communities. (November 2017) - Lingel, Jessa
In this article, I articulate a methodology for comparative qualitative analysis of online communities, which I refer to as networked field studies. I describe networked field studies as an approach that allows for looking across multiple communities and field sites to build a coherent set of analytical claims about the role of technology and everyday life, drawing on my own research investigating relationships to digital technologies among three countercultural communities. The major aim of this article is to contribute to methodological discussions on comparative qualitative analysis within Internet studies, foregrounding how research on digital technologies can both benefit from and complicate a comparative approach. After a brief summary of the communities studied in the research that has given rise to this methodological approach, I outline key methodological concepts and address the strengths and limitations of networked field studies as a method for analyzing socio-technical practices in everyday life.